ANALISIS EFEKTIFITAS PROGRAM PENGEMBANGAN WISATA PUNCAK WAKILA BERBASIS MASYARKAT DAN PENGUATAN UMKM DALAM TRANSFORMASI EKONOMI DESA KONDONGIA KECAMATAN LOHIA - Waode Purnama Megahsari; Jamaluddin Hos (Journal Publicuho, 2025)
This study aims to analyse the effectiveness of the community-based Puncak Wakila tourism development program in creating sustainable economic transformation in Kondongia Village, Lohia District. The research method uses mixed methods research with an explanatory sequential design, involving 245 respondents consisting of 109 community members, 40 MSME actors, and 96 tourists. Data were collected through questionnaires, in-depth interviews, observations, and FGDs, then analysed using the CIPP evaluation model and descriptive-inferential statistics. The results show a high level of community participation with a score of 3.89, dominated by very high cooperation participation (4.45). The program successfully drove MSME growth by 60.7% with the homestay sector leading growth at 80%, increased community income by 55.1%, and surged tourism services income by 143.1%. CIPP model evaluation shows good effectiveness with a score of 4.08, supported by increased tourist visits from 2,840 to 4,267 with an average growth of 22.6% per year. Main constraints include limited funding (3.67) and digital marketing capacity (3.52). The program proves effective in creating sustainable economic transformation, but requires strengthening innovative financing schemes, improving digital marketing capacity, and developing supporting infrastructure for optimal sustainability.